Editorial Preface - UTHM, Penerbit (International Journal of Integrated Engineering, 2018)
It is with great pleasure that we present the 6th regular issue of Volume 10 of the International Journal of Integrated Engineering (IJIE). The special issue of Data Information Engineering contains 30 papers contributed by 124 authors from various institutions. There topics covered in this issue including augmented reality, system testing, wireless area network, information security, data science and search engine optimization. There is also review on in silico-metabolic engineering, intrusion detection system and service-oriented architecture.The authors comprise researchers from four countries which are Malaysia, Indonesia, Pakistan and Iraq. Hopefully with all the strict reviewing process and selection, the knowledge presented will be helpful to the research community by providing breakthrough discoveries and future insight on where the research should be going.